User Experience on E-Government Online Services: A Case Study on The SIMPATIKA Service Application at The Ministry of Religious Affairs of Indonesia - Prakoso, Bondan Sapta; Subriadi, Apol Pribadi (Faculty of Computer Science (FILKOM) Brawijaya University, 2018)
User Experience (UX) is increasingly popular as a success factor in a product, system or service in many sectors and industries, including government institutions. User Experience Questionnaire (UEQ) is one of the tools at measure UX. The purpose of this study is to measure UX on the SIIMPATIKA Service Application as one type of E-Government Online Services in the Ministry of Religious Affairs of Indonesia. There are 127 employees of Indonesian Ministry of Religious Affairs participating in this research as respondent. The results of this study found that the SIMPATIKA Service obtained a very positive UX score on attributes of attractiveness, perspicuity, efficiency, dependability, and stimulation. However, novelty has a score quite positive than other attributes . The results of this study can be provides additional ideas for further development of the application of SIMPATIKA service at the Indonesian Ministry of Religious Affairs.